THE INFLUENCE OF INSTAGRAM CELEBRITY ENDORSEMENT ON PURCHASE INTEREST IN STUDENTS OF THE TRISAKTI TOURISM INSTITUTE - Anita Swantari; Haryo Wicaksono; Pramudito Pramudito (JPIM (Jurnal Penelitian Ilmu Manajemen), 2023)
This study aims to determine the effect of celebrity endorsements on Instagram on the buying interest of Trisakti Tourism Institute students. This research is a qualitative research that is quantified through a simple regression method. The population in this study were all Trisakti STP students, while the sample consisted of 100 respondents. The sampling technique used is accidental sampling. Data collection techniques by distributing questionnaires with a Likert scale. The results showed that celebrity endorsements on Instagram had a significant effect on the buying interest of Trisakti Tourism Institute students. Instagram celebrity endorsements significantly affect purchase intention among Trisakti Tourism Institute students because of their positive perceptions of Instagram celebrities as endorsers, their reputation and popularity, and the ease with which celebrities promote products or services on social media.